2011
DOI: 10.1007/s10802-011-9497-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Social Competence of Boys with Attention-Deficit/Hyperactivity Disorder: Problematic Peer Entry, Host Responses, and Evaluations

Abstract: Anecdotally and empirically, there is clear evidence that children with the Combined subtype of Attention-deficit/Hyperactivity Disorder (ADHD) experience disturbed peer relations, yet the field has not clearly established the origin of these difficulties. This is the first known investigation to examine the role of peer entry as a means to determine the social competence of boys with ADHD as they joined lab-based games played by age-mates who were good friends but unfamiliar with entry boys. Observational dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 35 publications
2
43
1
3
Order By: Relevance
“…These findings contradict those of previous studies [8,9], which identified children with NF1 and comorbid ADHD and/or learning problems as those most at risk for social problems. Additionally, ADHD is strongly associated with social incompetence in children without NF1 [53,54]. Our results are somewhat surprising and may represent a cohort effect in our relatively small sample.…”
Section: Discussioncontrasting
confidence: 58%
“…These findings contradict those of previous studies [8,9], which identified children with NF1 and comorbid ADHD and/or learning problems as those most at risk for social problems. Additionally, ADHD is strongly associated with social incompetence in children without NF1 [53,54]. Our results are somewhat surprising and may represent a cohort effect in our relatively small sample.…”
Section: Discussioncontrasting
confidence: 58%
“…However, a longer period for the retest (e.g., 6 months) is not an appropriate alternative because preschool children show fast developmental changes. Second, in the course of studying divergent clinical validity, in line with the Wakschlag, BriggsGowan, et al (2008) study, small but significant minor correlations were found between the majority of DB-DOS scores and parent reports of social skills on the SSRS; one may question whether the SSRS is an appropriate measure to examine divergent clinical validity, as social skills are less well developed in children with DBD and ADHD (Ronk, Hund, & Landau, 2011). Therefore we added the ECI-PDD part in view of studying divergent validity.…”
Section: Discussionmentioning
confidence: 90%
“…Results of the study indicated that boys with and without ADHD used the same number of competent peer entry strategies (e.g., synchronous behavior), but that boys with ADHD used twice as many attention-getting strategies (e.g., disruption) and talked significantly more about themselves than boys without ADHD (Ronk et al, 2011). Overall, boys with ADHD were rated as using an "excessive" number of high-risk entry strategies and received significantly fewer host invitations to enter play than their typically developing peers (Ronk et al, 2011). The absence of appropriate peer entry strategies utilized by boys with ADHD indicates a lack of appropriate social knowledge and sociocognitive skills.…”
Section: Journal Of Attentionmentioning
confidence: 96%